Age-Dependent Small-Animal Internal Radiation Dosimetry - Tianwu Xie; Habib Zaidi (Molecular Imaging)
Rats at various ages were observed to present with different radiosensitivity and bioavailability for radiotracers commonly used in preclinical research. We evaluated the effect of age-induced changes in body weight on radiation dose calculations. A series of rat models at different age periods were constructed based on the realistic four-dimensional digital rat whole-body (ROBY) computational model. Particle transport was simulated using the MCNPX Monte Carlo code. Absorbed fractions (AFs) and specific absorbed fraction (SAFs) of monoenergetic photons/electrons and S values of eight positron-emitting radionuclides were calculated. The SAFs and S values for most source-target pairs were inversely correlated with body weight. Differences between F-18 S values for most source-target pairs were between −1.5% and −2%/10 g difference in bodyweight for different computational models. For specific radiotracers, the radiation dose to organs presents a negative correlation with rat body weight. The SAFs for monoenergetic photons/electrons and S values for common positron-emitting radionuclides can be exploited in the assessment of radiation dose delivered to rats at different ages and weights. The absorbed dose to organs is significantly higher in the low-weight young rat model than in the adult model, which would result in steep secondary effects and might be a noteworthy issue in laboratory animal internal dosimetry.